2008
DOI: 10.1556/agrokem.57.2008.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A talajok vízellátottságának hatása a gazdasági növények vízigényének alakulására

Abstract: A növények életfeltételeit és termesztési lehetőségeit adott helyen alapvetően befolyásolják a meteorológiai viszonyok. Ezek között kiemelt jelentőséggel bírnak az egymással is sokrétű kölcsönhatásban álló energia- és vízellátottsági viszonyok. E tanulmányban a nagyobb változékonyságot mutató nedvességi viszonyok alakulásában megnyilvánuló törvényszerűségeket elemeztük a Nyugat-magyarországi Egyetem mosonmagyaróvári Matematika, Fizika és Informatikai Intézetének Meteorológiai Csoportja által létrehozott agrokl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, it is worthwhile to continuously supply the water uptaken from the soil. The soil can balance the extremes of the natural environment to a certain extent and to provide the plants with water and nutrients from the stored stocks at a certain level for a shorter or longer period (Vad et al, 2007;Varga-Haszonits et al, 2008). The year has a significant impact on the yield of maize, if the amount of precipitation is favourable during the season, outstanding yields can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is worthwhile to continuously supply the water uptaken from the soil. The soil can balance the extremes of the natural environment to a certain extent and to provide the plants with water and nutrients from the stored stocks at a certain level for a shorter or longer period (Vad et al, 2007;Varga-Haszonits et al, 2008). The year has a significant impact on the yield of maize, if the amount of precipitation is favourable during the season, outstanding yields can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The water demand of maize in the critical period is 350-500 mm. (Varga-Haszonits et al, 2008) The emergence of nutrition stock is significantly affected by the water resources of the soil. (Várallyay, 2002) In the long term experiments launched by Béla Gyırffy in Martonvásár the surveyed crop yields of corn-wheat biculture from 1958 and corn monoculture from 1959 showed that in dry cropyears a lower rate of fertilization resulted in higher yield stability in corn monoculture.…”
Section: Introductionmentioning
confidence: 99%